2019
DOI: 10.1002/ente.201801108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Cell Format on the Electrolyte Filling Process of Lithium‐Ion Cells

Abstract: During the production process of lithium‐ion battery cells, the filling, which consists of dosing and wetting steps, of the cell and its components with an electrolyte liquid is important for the quality and costs of the final product. The cell format as a combination of housing and cell arrangement not only determines the type of filling process but also influences the distribution of the electrolyte within the cell. The cell format also has an influence on the wetting state as a function of time. Herein, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…Geometrical defects generally have an influence on stacking and electrolyte filling. The internal cell structure of the lithium‐ion cell has a major influence on the electrolyte filling process . Any obstacles or deviations in shape interfere with the free electrolyte flow and hinder the complete wetting of the electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometrical defects generally have an influence on stacking and electrolyte filling. The internal cell structure of the lithium‐ion cell has a major influence on the electrolyte filling process . Any obstacles or deviations in shape interfere with the free electrolyte flow and hinder the complete wetting of the electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, local effects are to be expected here. For example, in a pouch cell, the flow of the electrolyte liquid was observed from three sides . If corrugations at the coating edge form, one or two sides are provided with shape deviations that can disturb the free flow of the electrolyte liquid.…”
Section: Resultsmentioning
confidence: 99%
“…With the help of neutron radiography, Günter et al. visualized the electrolyte distribution in pouch cells and proposed a pressure cycle wetting procedure to accelerate the electrolyte wetting ( Günter et al., 2019 ). To achieve a lower cost and better visualization, Deng et al.…”
Section: Current Manufacturing Processes For Libsmentioning
confidence: 99%
“…Neutron radiography recording during the filling process in a pouch cell with a z‐folded stack and a hardcase cell with a flat wound roll was performed. [ 143 ] It was found that during dosing, the electrolyte enters through the filling opening, and due to gravity, it accumulates in the empty space of the cell. The electrolyte then wets the cell assembly depending on the accessible axes of penetration, providing two and four wetting directions.…”
Section: Transforming Materials Into Practicalmentioning
confidence: 99%
“…The electrolyte then wets the cell assembly depending on the accessible axes of penetration, providing two and four wetting directions. [ 143 ] It was also observed that the most important factor during wetting seems to be the pressure cycles among flushing (with inert gas) and evacuation, multiple dosing, pumping (pressure cycles), and afterwetting. [ 143 ] The X‐ray based visualization of the filling process of LIBs was implemented and visually analyzing the recording, the parameters of the amount of entrapped gasses, the filling level, and the characteristics of the fluids flow front were derived.…”
Section: Transforming Materials Into Practicalmentioning
confidence: 99%